(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2023)
The aim of this paper is to recognize and re-envision strategies for peace education that encourage pluriversal and relational ways of knowing and being, and support the creation of a collective imagination of interdependence. One presumption is, that to realize cultures of peace it is crucial to transform the violences of modernity that encompasses a particular ontology and our mode of being in the world. The paradigm of modernity has universalized experience, grounding it in unitary ontologies and imperialist epistemologies that hinder certain systems of knowing and being. These epistemologies have heavily colonized our thinking and feeling, and consequently our educational systems. Embodied and holistic forms of learning and knowledge are marginalized in our current educational institutions. The paradigm of modernity traps us within a certain way of thinking about the world. How can peace education work with the unitary mode of thinking and the violences of modernity? I will try to frame a teaching and learning approach that enhances learners’ ability to think, feel and act critically, interdependently, and pluriversally, allowing for the coexistence of different worlds and realities. Pluriversality, the Zapatistas’ decolonial political vision, refers to a world in which many worlds coexist and various systems of knowing and being are given equal acknowledgement. The pluriverse tries to go beyond the dualistic, separatist ontology that focuses on human/nonhumans, mind/body, global south/global north, and developed/underdeveloped. The pluriverse calls for an ontoepistemological turn towards radical relationality and interdependence and this is especial crucial for peace (education).